HUBUNGAN ASUPAN SERAT, KEBIASAAN KONSUMSI JUNK FOOD, DAN DURASI TIDUR DENGAN GIZI LEBIH PADA REMAJA DI SMA YADIKA 12 LIMO TAHUN 2023 - Tasya Puteri Ayu, (2023)
Overweight is a condition when there is excessive accumulation of fat. Bad eating habits such as consumption of high calorie such as junk food, less fiber intake dan less sleep duration can lead to increased incidence of overweight in adolescents. The purpose of this study was to determine the relationship between fiber intake, junk food consumption habits, dan sleep duration with overweight in adolescents at Yadika 12 Limo High School. This study used a cross-sectional design with stratified rdanom sampling technique. The sample in this study was 117 participants with an age range of 15 - 17 years. Data collected in the form of weight dan height measurements, fiber intake using 2x24 hour recall, junk food consumption using the Food Frequency Questionaire (FFQ), dan sleep duration using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analysis in this study used chi-square test. The results of bivariate data analysis showed that there was an association between fiber intake (p = 0.008) dan junk food consumption habits (p = 0.008) with overweight but there was no association between sleep duration (p = 0.062) with overweight in adolescents at Yadika 12 Limo High School.